Pengembangan Modul Berbasis Learning Cycle 7E Berbantuan Video pada Materi Teori Kinetik Gas dan Termodinamika - Yuliana, Tia; Sari, Milya; Meria, Aziza (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
This research is motivated by the lack of availability of teaching materials using a scientific approach, the teaching materials used have not been able to visualize physical concepts that are abstract and the teaching materials used do not encourage students to read and train students' learning independence. The purpose of this study was to produce a 7E Video Cycle Learning Based Module on the valid, practical and effective Material of Kinetic Gas and Thermodynamics Theory. This research is a development research with Research & Development (R & D) approach. The development model used in this development is the Plomp development model which consists of three stages: Preliminary research, Prototype development and Development phase. Video-assisted Cycle 7E learning module on the material of gas and thermodynamic kinetic theory is very valid with an average score of 90.31% with a percentage of content feasibility test of 87.5%, language feasibility of 95% and media feasibility of 70.23%, where practicality by educators 89.2% and 89.4% of students. While effectiveness is categorized as very effective with an average score of 80.92%. From this development study it can be concluded that the 7E video-assisted learning cycle based module on the material of gas and thermodynamic kinetic theory has fulfilled the valid, practical and effective module qualifications to be used as an independent learning material for eleventh grade students of SMA / MA..